2018
DOI: 10.1038/s41598-018-19219-y
|View full text |Cite
|
Sign up to set email alerts
|

A neutral ceramidase, NlnCDase, is involved in the stress responses of brown planthopper, Nilaparvata lugens (Stål)

Abstract: Ceramidases (CDases) are vital enzymes involved in the biosynthesis of sphingolipids, which are essential components of eukaryotic membranes. The function of these enzymes in insects, however, is poorly understood. We identified a neutral ceramidase (NlnCDase) from the brown planthopper, Nilaparvata lugens, one of the most destructive hemipteran pests of rice. The C12-ceramide was the most preferred substrate for the NlnCDase enzyme. The activity of the NlnCDase enzyme was highest in the neutral-pH range (pH 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 59 publications
0
20
0
Order By: Relevance
“…This enzyme uses C12-ceramide as preferred substrate and displays optimal activity at pH6. The knock down of this enzyme enhanced survival of the female planthopper under high (32C) or low (22C) temperature (Shi et al, 2018). It is particularly exciting to see that distant homologues from nCDase are found in taxon all over evolution reinforcing a crucial role for ceramide.…”
Section: Basics Of Ncdasementioning
confidence: 99%
“…This enzyme uses C12-ceramide as preferred substrate and displays optimal activity at pH6. The knock down of this enzyme enhanced survival of the female planthopper under high (32C) or low (22C) temperature (Shi et al, 2018). It is particularly exciting to see that distant homologues from nCDase are found in taxon all over evolution reinforcing a crucial role for ceramide.…”
Section: Basics Of Ncdasementioning
confidence: 99%
“…Five human ceramidases, including acid ceramidase (AC/ASHA1), neutral ceramidase (NC/ASAH2), alkaline ceramidase 1 (ACER1), alkaline ceramidase 2 (ACER2), and alkaline ceramidase 3 (ACER3), encoded by five different genes, have been identified ( Coant et al, 2017 ). Acid, neutral, and alkaline ceramidases have been identified in insects ( Yoshimura et al, 2002 ; Monjusho et al, 2003 ; Yang et al, 2010 ; Zhou et al, 2011 ; Shi et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, CDases have been less extensively studied in insects rather than mammals ( Hannun and Obeid, 2011 ; Kraut, 2011 ; Mencarelli and Martinez Martinez, 2013 ). The enzymatic properties of the CDases in Tribolium ( Zhou et al, 2011 ), Laodelphax striatellus ( Zhou et al, 2013 ), and N. lugens ( Shi et al, 2018 ) have been characterized, but their biological roles remain poorly understood. Our previous study showed that NCER, the neutral CDase of N. lugens (NlnCDase), have a higher transcript levels and activity in adults and reproductive organs (ovaries and spermaries) ( Shi et al, 2018 ); however, NlnCDase’s biological functions in adults or tissue development are still unknown.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, ROS overproduction in human beings caused a variety of pathological consequences, such as atherosclerosis (Singh and Jialal 2006), diabetes (Piconi et al 2003), pulmonary fibrosis (Cheresh et al 2013), neurodegenerative disorders (Pitocco et al 2013), and arthritis (Wruck et al 2011). Neutral ceramidase is involved in the stress responses in brown planthopper (Nilaparvata lugens (Stål)) (Shi et al 2018) and alkaline ceramidase in Drosophila melanogaster associated to antioxidative stress capacity (Yang et al 2010). To protect themselves against harmful ROS, organisms increase ROS cleavage through upregulating the expression of antioxidants, which in turn neutralize the ROS and maintain ROS homeostasis (Pham-Huy et al 2008).…”
mentioning
confidence: 99%